2009
DOI: 10.1002/qj.376
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐platform observations of a springtime case of Bodélé and Sudan dust emission, transport and scavenging over West Africa

Abstract: ABSTRACT:The structure of the Saharan air layer over Niger and Benin during a major springtime dust event from the Bodélé region and Sudan is investigated using airborne lidar and dropsonde measurements. Aircraft operations were conducted on 13 and 14 June 2006, within the framework of the African Monsoon Multidisciplinary Analysis Special Observing Period. Complementary ground-based and satellite observations, as well as European Centre for Medium-range Weather Forecasts analyses are used to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 24 publications
8
52
0
Order By: Relevance
“…Indeed, in addition to the continental dust storms identified in March 2004 (Knippertz and Fink, 2006) and March 2006(Slingo et al, 2006Tulet et al, 2007), several meso-scale patterns of Saharan dust emissions and redistribution have been recently identified based on observations from the AMMA program (e.g. Flamant et al, 2007Flamant et al, , 2009BouKaram et al, 2008), the SAMUM experiments (Saharan Mineral Dust Experiment; May 2006; Morocco) (e.g. Knippertz et al, 2007Knippertz et al, , 2009 (Marsham et al, 2008).…”
Section: Dry Season Dust Eventsmentioning
confidence: 99%
“…Indeed, in addition to the continental dust storms identified in March 2004 (Knippertz and Fink, 2006) and March 2006(Slingo et al, 2006Tulet et al, 2007), several meso-scale patterns of Saharan dust emissions and redistribution have been recently identified based on observations from the AMMA program (e.g. Flamant et al, 2007Flamant et al, , 2009BouKaram et al, 2008), the SAMUM experiments (Saharan Mineral Dust Experiment; May 2006; Morocco) (e.g. Knippertz et al, 2007Knippertz et al, , 2009 (Marsham et al, 2008).…”
Section: Dry Season Dust Eventsmentioning
confidence: 99%
“…This approach does not apply to samples collected in the boundary layer during the monsoon season south of the ITCZ. In this case, the dominant flow is from the south-west: dust is present in the boundary layer only as a result of erosion by organised convection or under particularly stable conditions when high temperatures are established and the top height of the thermal turbulence in the boundary layer rises to or above the shear level, bringing dust from the free troposphere to the surface level (Flamant et al, 2009;Formenti et al, 2011b).…”
Section: Identification Of Source Regionsmentioning
confidence: 99%
“…In summertime, a mixture of Sudan and Chad sources, including Bodélé, may have been sampled (Flamant et al, 2009). Finally, a number of episodes of erosive emissions by convection in the Sahel were also sampled and characterised (referenced as Sahel).…”
Section: Identification Of Source Regionsmentioning
confidence: 99%
“…This underestimation may be due to the lack of east African sources in the simulation domain. For example, Flamant et al (2009) identified dust sensed over Niger in summer 2006 as mobilized from eastern African remote sources (Bodélé and Sudan) three days earlier. Therefore, the evaluation of the model skill in predicting dust in this area would benefit from a simulation with a larger domain.…”
Section: Export Of Dust Out Of Africamentioning
confidence: 99%